Noncommunicable diseases attributable to tobacco use in China: macroeconomic burden and tobacco control policies - Chen, Simiao; Kuhn, Michael; Prettner, Klaus; Bloom, David E. (Health affairs, 2019)
Smoking causes health problems for individuals and imposes a sizable macroeconomic burden on countries. As the world’s leading tobacco producer and consumer, China is at the epicenter of this health crisis. However, no studies have examined the macroeconomic burden of all relevant noncommunicable diseases (NCDs) attributable to tobacco or secondhand smoke exposure. We assessed how tobacco-attributable NCDs affect China’s productive capacity and estimated that these diseases would impose a total cost of 16.7 trillion yuan (US$2.3 trillion, in constant 2018 prices) in the period 2015-30, which corresponds to an annual tax of 0.9 percent on aggregate income. Secondhand smoke exposure accounts for 14 percent of the burden. If China raised the tax on cigarettes to 75 percent of their retail price and implemented wide-ranging tobacco-control policies, the Chinese economy could save 7.1 trillion yuan (US$1.0 trillion) for 2015-30—the equivalent of adding a 0.4 percent dividend annually.